Zagospodarowanie turystyczne w regionie kujawsko-pomorskim w aspekcie historycznym (Kronika Bydgoska, 2018)
The article presents several decades of activities in various forms of development of tourism in the region of Kuyavia and Pomerania, during the interwar period and after World War II all the way until 2018; starting from rather primitive forms of this development to more improved activities. Depending on local conditions and appropriate funds to implement various forms of this development and different investors (PTTK, social organizations and community budgets), we have obtained a wide range of effects and their adjustment to the needs and requirements of tourists in various forms of tourism development.